The impact of cumulative stress on asthma outcomes among urban adolescents. (April 2020) - Miadich, Samantha A.; Everhart, Robin S.; Greenlee, Jessica; Winter, Marcia A.
Abstract: Introduction: Many families living in low-income, urban areas experience a number of stressors (e.g., poverty, neighborhood stress, family functioning) that place adolescents at risk for worse asthma outcomes. Adolescents may face additional challenges (e.g., peer pressure, school stress) that add to their overall stress and influence their disease care and health outcomes. The current study examined the impact of a cumulative risk model of stressors including poverty, neighborhood stress, school stress, peer pressure, and caregiver-adolescent conflict on asthma outcomes (e.g., emergency department [ED] visits, asthma control, quality of life [QOL]) among urban adolescents (13–17 years). Methods: Data were collected from 61 urban families of adolescents with asthma (54.1% female; 93.4% African American) in the United States. Caregivers and adolescents completed questionnaires assessing stressors and asthma outcomes separately during a research session. Results: Cumulative risk was significantly associated with worse adolescent QOL and asthma control, and more ED visits. The cumulative risk index was also a more robust predictor of QOL and asthma control than any one individual predictor. Poverty, neighborhood stress, and school stress emerged as individual predictors of ED visits. Further, adolescents with well-controlled asthma had significantly lower neighborhood and school-related stress scores. Conclusions: Findings suggest that beyond the risk conferred by individual risk factors, an accumulation of stress can have an especially negative impact on asthma outcomes for urban adolescents. Future intervention work aimed at improving asthma outcomes should consider incorporating strategies for minimizing overlapping sources of stress in adolescents' daily lives.